Economic evaluation of an absorbable antibiotic envelope for prevention of cardiac implantable electronic device infection. Issue 5 (2nd December 2020) - Rennert-May, Elissa; Raj, Satish R; Leal, Jenine; Exner, Derek V; Manns, Braden J; Chew, Derek S
Abstract: Aims: Recent evidence suggests that an antibiotic impregnated envelope inserted at time of cardiac implantable electronic device (CIED) implantation may reduce risk of subsequent CIED infection compared with standard of care (SoC). The objective of the current work was to perform a cost-effectiveness analysis comparing an antibiotic impregnated envelope with SoC at time of CIED insertion. Methods and results: Decision analytic models were used to project healthcare costs and benefits of two strategies, an antibiotic impregnated envelope plus SoC (Env+SoC) vs. SoC alone, in a cohort of patients undergoing CIED implantation over a 1-year time horizon. Evidence from published literature informed the model inputs. Probabilistic and deterministic sensitivity analyses were performed. The primary outcome was the incremental cost per infection prevented, assessed from the Canadian healthcare system perspective. Envelope plus SoC was associated with fewer CIED infection (7 CIED infections/1000 patients) at higher total costs (29 033 000/1000 patients) compared with SoC (11 CIED infections and 27 926 000/1000 patients). The incremental cost per infection prevented over 1 year was 274 416. Use of Env+SoC was cost saving only when baseline CIED infection risk was increased to 6% (vs. base case of 1.2%). Conclusions: A strategy of Env+SoC was not economically favourable compared with SoC alone, and the opportunity cost of widescale implementation should be considered. Future work is required to develop validated risk stratification tools to identify patients at greatest risk of CIED infection. The value proposition of Env+SoC improves when applying this intervention to patients at greatest infection risk.